The impact of CHF/EUR exchange rate uncertainty on swiss exports to the Eurozone: Evidence from a threshold VAR1 - Julius Ferdinand Loermann (FIW - Research Centre International Economics, 2018)
In light of the recent discussion regarding the measurement of uncertainty and its impact on economic activity, this paper derives forward-looking measures of uncertainty and directional expectations for the CHF/EUR exchange rate based on over-the-counter option data and analyses its impact on exports. First, risk-neutral option-implied probability density functions are estimated and corrected for risk aversion. Second, the standard deviations of the densities are purged from uncertainty spillovers from the Eurozone. The resulting time series serves as a forwardlooking measure of exchange rate uncertainty, while the densities' skewness serves as a measure of directional expectations. Within a nonlinear threshold VAR framework, it is found that the exchange rate uncertainty measure defines a high uncertainty regime during recessions and market turmoil, and a low uncertainty regime during expansionary phases. Nonlinear impulse response analysis demonstrates that shocks to the exchange rate, the uncertainty and the directional expectations exhibit different dynamic impacts on exports during times of high and low uncertainty.
Keywords: C58; D84; E44; F31; 330; Swiss franc/Euro exchange rate; uncertainty shock; option-implied PDF; threshold VAR